The Effects of Pitavastatin on Nuclear Factor-Kappa B and ICAM-1 in Human Saphenous Vein Graft Endothelial Culture - Bulent Demir; Burak Onal; Sibel Ozyazgan; Esra Demir; Vedat Bakuy; Ahmet Gokhan Akkan (Cardiovascular Therapeutics)
Objective. To study pitavastatin’s effects on nuclear factor-kappa B (NF-κB ) and adhesion molecules in human saphenous vein graft endothelial culture indicating its pleotropic properties. Materials and Method. Low-dose (0.1 μM/L) and high-dose (1μM/L) pitavastatin calcium were administered as a frontline therapy in human saphenous endothelial cell culture, followed by induction of inflammation by TNF-α and determination of mRNA level alterations of ICAM-1 and NF-κB genes of endothelial cells using the qRT-PCR method. Additionally, immunofluorescence method was used to show the expression of NF-κB and ICAM-1. Finally, LDH levels were determined by the ELISA method to quantify cytotoxicity. Results. ICAM-1 mRNA expression in the low-dose pitavastatin+TNF-α group was significantly higher than that in the TNF-α group and significantly lower than that in the high-dose pitavastatin+TNF-α group (for all comparisons, P = 0.001). The low-dose pitavastatin+TNF-α group had a similar NF-κB mRNA expression with TNF-α and high-dose pitavastatin+TNF-α groups. Conclusion. Pitavastatin increases ICAM-1 mRNA expression in saphenous vein endothelial cells. Furthermore, the effect of pitavastatin on adhesion molecules appears independent of NF-κB. Novel studies are needed in this field.